Management of green mould of oyster mushroom by garlic extract - and K.C. PUZARI, M.K. NARZARI, ROBIN GOGOI* (Indian Phytopathology, 2007)
Contamination of oyster mushroom beds caused by green mould fungus Trichoderma harzianum was attempted to manage using extracts of consumable and non-consumable onion (Allium cepa L.) and garlic (A. sativum L.). In vitro, 7.5% onion extract completely inhibited the mycelial growth of T. harzianum while 5% extracts of consumable and non-consumable onion could inhibit 88.6 and 83.0% mycelial growth, respectively. In case of garlic, complete inhibition of T. harzianum was obtained by 0.4% extract while 0.2% extract of consumable and non-consumable garlic inhibited the green mould by 42.2 and 12.2%, respectively over control. Spraying of 0.3, 0.4 and 0.5% garlic extract on the pasteurized straw before spawning resulted 69.6, 77.5 and 78.3 % increased yield, and while sprayed after opening the beds, they contributed 28.3, 34.3 and 37.9% increased yield respectively over control. Carbendazim (0.1%) sprayed during spawning and after opening the beds produced 79.4 and 38.9% increased yield, respectively. Mushroom yield obtained in 0.5% garlic extract and 0.1% carbendazim was statistically at par.